2005
DOI: 10.1074/jbc.m506191200
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Two Clip Domain Serine Proteases in Innate Immune Responses of the Malaria Vector Anopheles gambiae

Abstract: The malaria vector Anopheles gambiae is capable of multiple immune responses against Plasmodium ookinetes. Accumulating evidence in several insect species suggests the involvement of serine protease cascades in the initiation and coordination of immune responses. We report molecular and reverse genetic characterization of two mosquito clip domain serine proteases, CLIPB14 and CLIPB15, which share structural similarity to proteases involved in prophenoloxidase activation in other insects. Both CLIPs are express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(118 citation statements)
references
References 37 publications
6
112
0
Order By: Relevance
“…While biochemical functions are unknown for most of these clip-domain serine proteinases, Northern blot and RT-PCR analyses revealed that the mRNA levels of HP2, HP13, HP18, HP21, and HP22 increased in the larval fat body and/or hemocytes after a bacterial injection, suggesting that these enzymes all play certain roles in defense responses . Due to higher sequence similarities with PAPs, current research on melanization in A. gambiae is focused on members of the B group (Volz et al, 2005;Paskewitz et al, 2006). RNA interference tests showed close associations of ClipB4, ClipB8, ClipB14, and ClipB15 with melanization of Sephadex beads or Plasmodium ookinetes.…”
Section: Discussionmentioning
confidence: 99%
“…While biochemical functions are unknown for most of these clip-domain serine proteinases, Northern blot and RT-PCR analyses revealed that the mRNA levels of HP2, HP13, HP18, HP21, and HP22 increased in the larval fat body and/or hemocytes after a bacterial injection, suggesting that these enzymes all play certain roles in defense responses . Due to higher sequence similarities with PAPs, current research on melanization in A. gambiae is focused on members of the B group (Volz et al, 2005;Paskewitz et al, 2006). RNA interference tests showed close associations of ClipB4, ClipB8, ClipB14, and ClipB15 with melanization of Sephadex beads or Plasmodium ookinetes.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, RNA interference studies indicate that more than one melanization pathway is induced in response to infection in A. gambiae (11,14).…”
Section: Discussionmentioning
confidence: 99%
“…hemocytes are recruited to the midgut and dorsal vessel during Plasmodium sp. infection (Volz et al, 2005;Rodrigues et al, 2010;King and Hillyer, 2012), and may mediate innate 'immune memory' (Rodrigues et al, 2010). However, despite the multi-faceted contribution of mosquito hemocytes to immunity against malaria parasites, little is known about their basic biology.…”
Section: Research Articlementioning
confidence: 99%